Effect of breed and reproductive management on fertility traits in robotic milking system - Holló, Gabriella; Bús, Bence; Szabari, Miklós (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
This paper aimed at presenting the reproductive performance of two dairy breeds (Holstein, Hungarian Simmental) with different cow treatment approach (estrus synchronisation: 50-60 days postpartum, estrus synchronisation: 90-100 days postpartum, non-synchronized) in robotic milking system. Records for 6610 milking of 807 lactating dairy cows from 3 commercial dairy farms were analyzed. Later breeding synchronized (90-100 days post partum) Simmental had the lowest number of services per conception. The shortest calving to first service interval was detected for first breeding synchronized (50-60 days postpartum) Holstein cows. The overall pregnancy rate were shown to range between 39.2% and 57.7%. Proportion of primiparous cows confirmed pregnant within 90 days postpartum varied from 46.5% to 70,8%. Comparing milk-based traits of cows with different reproductive status within 150 days in milk can be seen a highly signiﬁcant inﬂuence of milk yield, the average protein content on reproductive status of cows in case of all herds. Finding reveal high-producing Holstein had the poorer fertility features, however synchronization seemed to affect reproductive traits more favorable in primiparous cows. The differences in fertility caused changes in some milk-based traits; however, these results should be confirmed further investigations.